Unlocking the antiviral potential of rosmarinic acid against chikungunya virus via IL-17 signaling pathway - Liao, Xinfei; Xin, Jialiang; Yu, Ziping; Yan, Weiming; Li, Chenghui; Cao, Liang; Zhang, He; Wang, Wei (Frontiers in Cellular and Infection Microbiology, 2024)
Background The Chikungunya virus is an Alphavirus that belongs to the Togaviridae family and is primarily transmitted by mosquitoes. It causes acute infection characterized by fever, headache, and arthralgia. Some patients also experience persistent chronic osteoarthritis-like symptoms. Dedicated antiviral treatments are currently unavailable for CHIKV. This study aims to explore the potential anti-CHIKV effect of rosmarinic acid using network pharmacology. Methods This study employed network pharmacology to predict and verify the molecular targets and pathways associated with ROSA in the context of CHIKV. The analysis outcomes were further validated using molecular docking and in vitro experiments. Results The analysis of CHIKV targets using the Kyoto Encyclopedia of Genes and Genomes and MCODE identified IL-17 as an important pathogenic pathway in CHIKV infection. Among the 30 targets of ROSA against CHIKV, nearly half were found to be involved in the IL-17 signaling pathway. This suggests that ROSA may help the host in resisting CHIKV invasion by modulating this pathway. Molecular docking validation results showed that ROSA can stably bind to 10 core targets out of the 30 identified targets. In an in vitro CHIKV infection model developed using 293T cells, treatment with 60 μM ROSA significantly improved the survival rate of infected cells, inhibited 50% CHIKV proliferation after CHIKV infection, and reduced the expression of TNF-α in the IL-17 signaling pathway. Conclusion This study provides the first confirmation of the efficacy of ROSA in suppressing CHIKV infection through the IL-17 signaling pathway. The findings warrant further investigation to facilitate the development of ROSA as a potential treatment for CHIKV infection.